(untitled) (London Journal of Research In Management & Business, 2024)
This study investigates the Environmental, Social, and Governance (ESG) disclosure practices, employing content analysis to evaluate ESG reports. Data were collected from companies listed on the Athens Stock Exchange, and the analysis revealed significant inconsistencies in ESG reporting due to the absence of a standardised ESG taxonomy. Some firms adopt quantitative criteria, while others rely on qualitative approaches, complicating comparisons. Using both qualitative and quantitative content analysis, this research identified the need for a unified ESG framework to enhance transparency, investor trust, and regulatory compliance. The findings suggest that annual ESG reporting is essential for improving corporate transparency and accountability, particularly in emerging markets like Greece. The study contributes to institutional theory by emphasising the transitional phase of ESG institutionalisation, while stakeholder theory highlights the importance of transparent ESG reporting for fostering stakeholder trust. The discussion suggests that regulatory frameworks and stakeholder pressures are crucial in promoting consistent and transparent ESG disclosures. This research underscores the need for harmonised reporting practices to support corporate legitimacy and long-term sustainability.